Company’s Behavior, Time Factor and Teleological Logic in Relevant Market Definition under Morocco–EU Law - Mohamed El Azhary (European Scientific Journal, ESJ, 2026)
This study explores the legal and economic foundations of the concept of the relevant market within the Moroccan and European Union competition law systems. It proceeds from the idea that both Moroccan Law No. 104-12 and the EU framework under Articles 101 and 102 TFEU require a precise delineation of the competitive space in which undertakings operate in order to ensure the effective enforcement of competition rules. The objective is to analyse how competition authorities in Morocco and within the EU define the relevant market to identify competitive constraints, assess corporate behaviour, and determine whether practices such as cartels or abuses of dominant position are capable of preventing, restricting, or distorting free competition.Methodologically, the research adopts a comparative and analytical approach, combining legal interpretation, industrial economics principles and organisational analysis. It draws on the Structure-Behaviour-Performance paradigm, integrates both macro- and microeconomic considerations, and incorporates temporal and finalistic dimensions that influence the deployment of undertakings within their respective competitive environments. This multidisciplinary method provides a clearer understanding of how market definition functions as both a normative requirement and a factual diagnostic tool.The findings reveal three decisive factors that shape a pragmatic understanding of the relevant market in both systems: the structuring role of corporate behaviour; the importance of temporal factors, as cartels and dominance assessments rely on past and present market conditions; and the relevance of purpose, since the strategic intent of undertakings is essential for evaluating anti-competitive effects.